Semiclassical approximation to the propagator of the Wigner function for particles in confined spaces (2017)
Abstract: This work constructs the exact Wigner propagator for particles confined by one or two infinitely high potential walls. It takes advantage of the limit of polynomial potentials so as to obtain the semiclassical approximation for smooth potentials close to the box with two walls